2022
DOI: 10.37040/geografie.2022.006
|View full text |Cite
|
Sign up to set email alerts
|

Cartographic scripts for seismic and geophysical mapping of Ecuador

Abstract: This research describes a script-based method of Generic Mapping Tools (GMT) for mapping the seismicity, geophysics, geology and topography of Ecuador. The advances of GMT include the following points: (1) automation of workflow; (2) refined aesthetics of graphics; (3) speed console-based mapping; (4) multi-format data handling; (5) advanced syntax. An explanation of scripting with the examples of code snippets is provided. The results present six new maps of Ecuador. The distribution of geophysical phenomena … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 84 publications
0
4
0
Order By: Relevance
“…Such an approach demonstrated that the inclusion of scripts speeds up cartographic plotting and image processing and facilitates the research methodology. As mentioned earlier [106], the main advantage of scripts consists in automation of the process and repeatability of the workflow, which saves time. Using the information received from the automated image analysis and interpretation, we were able to detect the changes in the analysis of the landscapes of eastern Mozambique for evaluation of the environmental effects from climate change.…”
Section: Scriptingmentioning
confidence: 99%
“…Such an approach demonstrated that the inclusion of scripts speeds up cartographic plotting and image processing and facilitates the research methodology. As mentioned earlier [106], the main advantage of scripts consists in automation of the process and repeatability of the workflow, which saves time. Using the information received from the automated image analysis and interpretation, we were able to detect the changes in the analysis of the landscapes of eastern Mozambique for evaluation of the environmental effects from climate change.…”
Section: Scriptingmentioning
confidence: 99%
“…This is achieved through the advanced methods of machine learning (ML) [33][34][35][36]. Among them, scripting techniques enable handling RS data effectively and accurately [37][38][39][40][41][42]. An essential advantage of the programming languages consists of automation of the RS data processing.…”
Section: Related Workmentioning
confidence: 99%
“…In contrast to traditional GUI-based GIS methods, cartographic scripts do not directly generate maps. However, they provide a series of commands that encompass crucial information about the map's appearance, governing specific features on a plotted cartographic layout [16]. In fact, scripts and programming commands used in cartography define the elements present on the map produced by the script during execution.…”
Section: Introduction 1backgroundmentioning
confidence: 99%